Kinerja Karyawan dalam Perspektif Ekonomi Islam: Gaya Kepemimpinan, Loyalitas, dan Keahlian (Studi Empiris di SAMSAT Kota Langsa) - Ibnah Ibnah; Zikriatul Ulya Zikri; Mastura Mastura; Ade Fadillah Fw Pospos (Journal Research of Economic and Bussiness, 2026)
As demands for quality public services increase, employee performance has become a critical factor in determining the success of public sector organizations, including service agencies based on Islamic economic values. This study aims to analyze the influence of leadership style, loyalty, and expertise on employee performance from an Islamic economic perspective at the Langsa City SAMSAT Office. The study used a quantitative approach with a survey method. The study population consisted of 21 employees, all of whom were sampled using a total sampling technique. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that leadership style partially has a positive but insignificant effect on employee performance. Loyalty also has a negative and insignificant effect on employee performance. Conversely, expertise has a positive and significant effect on employee performance. However, leadership style, loyalty, and expertise simultaneously have a significant effect on employee performance. The adjusted R² value of 0.662 indicates that the three independent variables explain 66.2 percent of employee performance, with the remainder influenced by other variables outside the research model. From an Islamic economic perspective, these findings confirm that expertise (itqān) is a dominant factor in improving employee performance, which requires trustworthy leadership and work loyalty based on religious intentions. This research is expected to contribute to the development of human resource management based on Islamic economic values ​​in the public service sector. Keywords: Leadership Style, Loyalty, Expertise, Employee Performance, Islamic Economics